Model Layanan untuk Mendukung Pembelajaran Transdisipliner - Dwi Soca Baskara; Sulton Sulton; Henry Prahedhiono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: Transdisciplinary approach are present to address today’s learning needs. The needs comes along side with global culture that change rapidly, unpredictable, and discipline that always affected by any other discipline. University as a academic society must provide appropriate learning service. Such provision is in line with the ideals of State University of Malang and the needs of Educational Technology Department. In this study was conducted an analysize of the transdisciplinary learning service model needs. Based on questionaries that have been disseminated, it is known that students of educational technology need a transdisciplinary learning service model. So it will create integrated transdisciplinary learning activities.Abstrak: Pendekatan transdisipliner hadir untuk memenuhi kebutuhan belajar masyarakat kekinian. Perubahan budaya global yang sangat pesat dan tak terduga, serta keilmuan yang tidak dapat berdiri pada posisi parsial merupakan faktor pemicu kebutuhan tersebut. Perguruan tinggi sebagai wujud masyarakat akademik dituntut untuk memberikan layanan pembelajaran yang sesuai. Pemberian layanan tersebut sejalan dengan cita-cita Universitas Negeri Malang dan kebutuhan program studi Teknologi Pendidikan. Dalam penelitian ini dilakukan analisis kebutuhan model layanan pembelajaran transdisipliner. Berdasarkan angket yang disebarkan pada alumni mahasiswa Teknologi Pendidikan diketahui bahwa mahasiswa membutuhkan model layanan pembelajaran transdisipliner yang dapat menciptakan kegiatan belajar lintas disiplin tersistem dan terintegrasi.